2015
DOI: 10.1007/s00246-015-1248-8
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the 4p16 Susceptibility Locus and the Risk of Atrial Septal Defect in Population from Southeast China

Abstract: Three single nucleotide polymorphisms (SNPs), rs16835979, rs870142 and rs6824295, located in chromosome 4p16 were associated with the risk of ostium secundum atrial septal defect (ASD) in the European population. The 4p16 susceptibility locus in congenital heart disease was replicated in Chinese populations. Here, we analyzed the associations between these three SNPs and ASD in Chinese population from Fujian Province in southeast China. We conducted a case-control study by genotyping three SNPs in 354 non-synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…9 replicated the results in Han Chinese subjects (two cohorts, totaling 701 ASD cases and 3,208 controls); next, a similar outcome was observed in a sample from Southwest China (190 ASD cases and 225 controls) 10 ; and more recently, Pei et al . 11 reported analogous findings in a Fujian Chinese population (354 non-syndromic ASD cases and 557 controls).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…9 replicated the results in Han Chinese subjects (two cohorts, totaling 701 ASD cases and 3,208 controls); next, a similar outcome was observed in a sample from Southwest China (190 ASD cases and 225 controls) 10 ; and more recently, Pei et al . 11 reported analogous findings in a Fujian Chinese population (354 non-syndromic ASD cases and 557 controls).…”
Section: Introductionsupporting
confidence: 56%
“…The design by Pei et al . 11 was well powered to detect the effect they found (OR of 1.431, power close to 90%). Overall, pooled effect size estimates from the meta-analysis should be interpreted with caution, considering the evidence of bias from the contour-enhanced funnel plot.…”
Section: Resultsmentioning
confidence: 95%
“…European-ancestry samples: a discovery cohort of 340 individuals with ostium secundum ASD and 5,159 controls, and a further 417 secundum ASD cases with 2,520 controls. Independent studies in Chinese cohorts have provided additional support to that finding: Zhao et al 7 replicated the results in Han Chinese subjects (two cohorts, totaling 701 ASD cases and 3,208 controls); next, a similar outcome was observed in a sample from Southwest China (190 ASD cases and 225 controls) 8 ; and more recently, Pei et al 9 reported analogous findings in a Fujian Chinese population (354 non-syndromic ASD cases and 557 controls). Demographic data on sex and age distributions across diagnoses is summarized in Supplementary Table S1, organized as "controls" (subjects with no evidence of CHD), "LVOTO" (including both LVOTO and bicuspid aortic valve, BAV), "any ASD" (comprising participants with either a pure ASD diagnose, or an ASD and another CHD condition), or "pure ASD" (a subset of "any ASD": people with evidence of ASD, but no other CHD).…”
Section: In Twomentioning
confidence: 80%
“…Power was higher in the study by Zhao et al 8 (~69%); however, they reported an unusual MAF of 28.7% in their controls as opposed to the 33% values reported by the other Chinese groups, which may indicate strong differences in ancestry of the participants. The design by Pei et al 9 was well powered to detect the effect they found (OR of 1.431, power close to 90%). Overall, pooled effect size estimates from the meta-analysis should be interpreted with caution, considering the evidence of bias from the contour-enhanced funnel plot.…”
Section: Resultsmentioning
confidence: 97%
“…Of the remaining 16 SNPs identified in the infant-only casecontrol discovery analysis with p < 1 Â 10 À5 , several are in genomic regions previously reported to be associated with atrial septal defects in other GWAS analyses, including 4p16 (Cordell et al, 2013;Pei et al, 2016;B. Zhao et al, 2014;L.…”
Section: Discussionmentioning
confidence: 99%